Distance learning of languages - Masakova, G.A.; Aytbayeva, B.M.; Maulenova, A.M. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The article explores theoretical approaches to the use of distance technologies in the teaching of languages. The authors consider remote technology as a way of learning. The possibilities of distance learning should be widely used in teaching the language. This is a very effective technology for language learners, because with distance learning the listener can work independently at a convenient time in a convenient place with an effective pace. That is, the advantages of distance learning, which allow the use of external information for adults who work in a group and study in terms of their schedule, are inconvenient. Therefore, students should know the technique and technique of work, the basis for self-enrichment of knowledge at the highest level. At the same time, it should be able to work with new tools in the field of information technology for effective study.
Тілдерді қашықтықтан оқыту
Дистанционное обучение языкам
Keywords: training; remotely; teaching; internet; language; distance education; technologies; innovation